Ocupação de fundos de vale em áreas urbanas. Estudo de caso: Córrego do Mineirinho, São Carlos, SP - Amorim, Lia Martucci de (2004)
In the last 50 years, the Brazilian urban growth process is compromising in many ways the environmental quality of the cities. Thus, among several impacts existents, it s possible to notice an inadequate occupation of river marginal areas. This is causing modifications in the physical and biological environmental elements, wasting potential recreation areas and bringing several problems to the urban population, like inundation and flood. The purposes of this research were to investigate and discuss environmentally correct alternatives to river marginal areas occupation. There were developed environmental criteria to provide solid basis for planning the land use of these areas. Based on these criteria, an example of local characteristics evaluation method was proposed. This method was applied to the chosen object of study - Mineirinho stream marginal area - in the city of São Carlos-SP-Brazil. The main results obtained were the studied area environmental situation diagnosis and some suggestions of occupation or restoration.